Beginning Object-Oriented Programming with VB 2005 - Clark, Daniel R. (Apress, 2012)
This book provides you with the information needed to understand how you go about architecting an object-oriented programming solution aimed at solving a business problem. As you work your way through the book, first you will learn how to analyze the business requirements. Next, you will model the objects and relationships involved in the solution design. Finally, you will implement the solution using Visual Basic .NET. Along the way, you will learn the fundamentals of software design, the Unified Modeling Language (UML), object-oriented programming, Visual Basic (VB), and the .NET Framework. Because this is an introductory book, it is meant to be a starting point for your study of the topics presented. As such, this book is not designed to make you an expert in object-oriented programming and UML; nor be an exhaustive discussion of VB and the .NET Framework; nor be an in-depth study of Visual Studio. It takes considerable time and effort to become proficient in any one of these areas. It is my hope that by reading this book, your first experiences in objectoriented programming will be enjoyable, comprehensible, and instill a desire for further study